Good Environmental Governance dalam Pengelolaan Sampah di Kota Pekanbaru - Putri, Selphi Afdayati Dwi; Heriyanto, Meyzi; As’ari, Hasim (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This research is motivated by the high population growth in Pekanbaru City, Riau Province. This growth has led to various issues, one of which is the daily increase in waste generation. Considering Pekanbaru's limited waste management capacity, a sustainable and environmentally conscious approach is necessary. This study aims to analyze and explore the application of good environmental governance in waste management in Pekanbaru City and to identify the challenges faced. The theoretical framework used is Belbase's good environmental governance theory, which includes seven indicators: rule of law, participation and representation, access to information, transparency and accountability, decentralization, institutions and organizations, and access to justice. The research employs a qualitative approach based on postpositivist philosophy, using data triangulation for data collection. Data analysis in this research involves three stages: data condensation, which is done by selecting key informants; data presentation, which summarizes responses from each informant; and conclusion drawing. The findings indicate that waste management in Pekanbaru City does not yet meet the principles of Good Environmental Governance. The challenges include policy changes, lack of environmental awareness, and the absence of a structured waste management system.